Native circulating Brucella melitensis lineages causing a brucellosis epidemic in Qinghai, China - Xue, Hongmei; Zhao, Zhijun; Wang, Jianling; Ma, Li; Li, Jiquan; Yang, Xuxin; Ren, Lingling; Xu, Liqing; Liu, Zhiguo; Li, Zhenjun (Frontiers in Microbiology, 2023)
Since 2010, the cases and incidences of human brucellosis have been increasing annually in Qinghai (QH) Province. Molecular epidemiology and phylogenetic analyses of strains from this region are crucial to better understand the transmission of the disease and the evolutionary patterns of Brucella strains. In this study, classical bio-typing assay, multilocus variable-number tandem repeat analysis, and the whole-genome sequencing–single-nucleotide polymorphism approach were used to illustrate the epidemiological and evolutionary patterns of Brucella melitensis. A total of 54 B. melitensis bv. 3 strains were isolated and molecularly characterized, with all strains belonging to the East Mediterranean lineages. Cross-regional transmission events (i.e., between counties) were caused by common sources of infection, suggesting that predominant circulating genotypes are endemic in different regions. Strengthening surveillance in animal brucellosis and controlling infected animals’ cross-border movement are necessary. Two strains isolated from humans and marmots were clustered in the same sub-clade, implying the possible existence of direct and/or indirect contact between sheep (and goats) and wildlife (marmots), but this needs to be verified by further investigations. The global-scale phylogenetic analysis indicated that 54 strains sorted into six subclades, four of which formed independent lineages, suggesting that the increase in the incidence rate of human brucellosis may be caused by local circulating lineages. Further strengthening the serology and pathogen surveillance of animals (wildlife) and humans will contribute to an in-depth understanding of the transmission chain of human brucellosis in this region.